Geriatric Assessment of Older Patients with Cancer: Recent Data and Updated Recommendations - Vérène Dougoud; Marcus Vetter (healthbook TIMES. Oncology Hematology)
One pivotal question in geriatric oncology pertains to the precise assessment of the current functional status of elderly patients in order to define the treatment goals, optimize the treatment outcomes and preserve the quality of life (QoL). The geriatric assessment (GA) is recognized as a solution for developing a coordinated and integrated treatment plan for older patients with cancer. However, is there clinically proven evidence that GA helps in managing older patients with cancer? This paper focuses on recent data demonstrating the benefits of GA and GA-driven interventions on clinical outcomes of geriatric patients with cancer.